Ensino médio: função do estado ou da empresa? - Whitaker, Dulce Consuelo Andreatta [UNESP]; Fiamengue, Elis Cristina [UNESP] (Centro de Estudos Educação e Sociedade (CEDES), 2001)
O presente artigo levanta questões importantes acerca da qualidade do ensino médio público quando comparado ao particular, a partir de dados da pesquisa 10 anos depois: Unesp - Diferentes perfis de candidatos para diferentes cursos (Estudo de variáveis de capital cultural), questionando a visão ideológica de que a escola particular coloca seus alunos mecanicamente nas melhores universidades. Apresentando dados sobre a performance dos candidatos ao vestibular oriundos do sistema particular e do sistema público, o artigo mostra que, nos dois casos, a freqüência a cursinhos é uma constante, o que coloca em xeque a tão propalada maior qualidade do ensino médio particular.

The present paper discuss important subjects concerning the quality of the public high school when compared to the private, starting from data of the research 10 years later - Unesp - candidate's different profiles for different courses (Study of variables of Cultural Capital), questioning the ideological vision that the private school places your students mechanically in the best Universities. Presenting data on the performance of candidates to the vestibular examination originating from of the private system and of the public system, the article shows that in the two cases the frequency to preparatory courses is a constant, what places so in check the supposed best quality of the private high school.
Secondary school: a matter of state or enterprise?
Keywords: Ensino Médio; Ensino Médio Particular e Público; Efeito Cursinho; Acesso à Universidade; Secondary School; State or Business Secondary School; Preparatory course effect; University admittance